(untitled) (Bioresearch Communications, 2026)
Background: Soil salinity and water scarcity are significant constraints to rice production in coastal agroecosystems, where plants frequently encounter combined salt and moisture stress, particularly in the dry season. This study evaluated the effects of crop residue-based organic amendments such as rice straw compost (RSC), sawdust (SD), rice husk (RH), and mustard seed meal (MSM) on nutrient uptake and Na⁺/K⁺ homeostasis in two contrasting rice genotypes, BRRI Dhan 28 (salt-sensitive) and BRRI Dhan 47 (salt-tolerant), under full and deficit irrigation regimes. Methods: A split-split plot field experiment was conducted during the dry season in salt-affected coastal soils of Khulna, Bangladesh. Findings: Organic amendments significantly (p ≤ 0.05) improved the uptake of macro- (N, P, K, S, Ca, Mg) and micronutrients (Fe, Mn, Zn) in both genotypes. The MSM enhanced N, Ca, and Mg accumulation, while RSC and SD effectively increased K+ and S uptake. All amendments markedly reduced the Na⁺/K⁺ ratio, improving ionic balance and alleviating salinity-induced toxicity. Correlation analyses indicated strong positive associations among key nutrients and significant negative relationships between Na⁺/K⁺ ratios and nutrient contents, underscoring the role of amendments in optimizing nutrient dynamics. Conclusion: These findings demonstrate that integrating crop residue-based organic amendments into salt-affected coastal soils enhances nutrient availability, maintains ionic homeostasis, and mitigates combined salt and water deficit stress in rice. Adopting such sustainable practices offers a promising pathway for improving soil health, boosting rice productivity, and strengthening climate resilience in vulnerable coastal agroecosystems. Bioresearch Commu. 12(1): 1895-1912, 2026 (January)